2020
DOI: 10.1111/jocd.13312
|View full text |Cite
|
Sign up to set email alerts
|

Noncultured epidermal suspensions obtained from partial‐thickness epidermal cuts and suction blister roofs for vitiligo treatment: A prospective comparative study

Abstract: Background The treatment options for vitiligo are either nonsurgical, including medical treatments and phototherapy, or surgical, including autologous transplantation methods. Noncultured epidermal suspension transplantation is indicated for the treatment of stable vitiligo not responding to either medical treatment or phototherapy. Variable results have been reported for the various techniques used for the preparation of this suspension. Aim To compare the outcome between suction blister roof grafts and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Our research group clinically evaluated the pigmentation outcome in nonsegmental stable vitiligo patients treated by NCES prepared by both techniques was done by our research group. The study revealed a comparable repigmentation results with no statistical difference between the two groups 3 . This is supported by the fact that the number of keratinocytes and melanocytes in the suspension was also more or less the same with no statistical difference 4…”
Section: Discussionsupporting
confidence: 59%
“…Our research group clinically evaluated the pigmentation outcome in nonsegmental stable vitiligo patients treated by NCES prepared by both techniques was done by our research group. The study revealed a comparable repigmentation results with no statistical difference between the two groups 3 . This is supported by the fact that the number of keratinocytes and melanocytes in the suspension was also more or less the same with no statistical difference 4…”
Section: Discussionsupporting
confidence: 59%
“…We analyzed a total of 117 unique studies with 8776 unique patients (eTable 1 in the Supplement), including 19 studies with 1631 patients in the punch grafting group, 10 studies with 718 patients in the thin skin grafting group, 29 studies with 2652 patients in the suction blister grafting group, 45 studies with 2209 patients in the noncultured epidermal cell suspension (NCES) group, 9 studies with 185 patients in the noncultured follicular cell suspension (NCFS) group, and 17 studies with 1381 patients in the cultured epidermal cell suspension (CES) group; 11 studies included more than 1 procedure type. The median follow-up duration was 7 (range, 2-108) months.…”
Section: Resultsmentioning
confidence: 99%
“…In 2008, Awad 9 used a Chinese cupping device to induce blisters for NCES transplantation without any cosmetic disfigurements at the donor sites. Recently, Anbar et al 21 reported no significant difference in the clinical outcome between NCES prepared from partial‐thickness epidermal cuts and those prepared from suction blisters induced by a Chinese cupping device. However, patients underwent the former technique showed hyperpigmentation in two patients and variable degrees of scarring in 18 patients, while all patients underwent the latter technique showed hyperpigmentation at the donor sites that faded over time.…”
Section: Discussionmentioning
confidence: 99%